Case Report: Novel IRF2BP2 variant in a Japanese patient with impaired B-cell differentiation, Th1 polarization, and systemic immune dysregulation - Endo, Yushiro; Koga, Tomohiro; Kurushima, Shota; Tomokawa, Takuya; Mishima, Hiroyuki; Yoshiura, Koh-ichiro; Matsumoto, Tadashi; Kawakami, Atsushi (Frontiers in Immunology, 2025)
Interferon regulatory factor 2 binding protein 2 (IRF2BP2) is a transcriptional corepressor involved in immune regulation via IRF1-mediated interferon signaling inhibition. Pathogenic IRF2BP2 variants are associated with common variable immunodeficiency, primarily affecting B-cell maturation. We report a 47-year-old female with immunodeficiency and systemic inflammation, including primary biliary cholangitis and unclassified arthritis, who was detected to carry a novel heterozygous de novo missense variant in the IRF2BP2 gene (c.1663T>A; p. Cys555Ser). Immunophenotyping revealed naïve B-cell predominance, with a loss of memory B cells and impaired plasmablast differentiation, indicating late-stage disturbed B-cell differentiation/maturation. CD4+ T cells demonstrated Th1 polarization with reduced Th2 subsets, whereas Th17 and Treg populations exhibited no obvious changes. Considering that IRF2BP2 negatively regulates STAT1-driven transcription via IRF1 suppression, the observed Th1 polarization suggests improved STAT1 activity. This case underscores the combined humoral and cellular immune dysregulation due to IRF2BP2 dysfunction, expanding the clinical spectrum to encompass inflammatory phenotype.